P EMETAAN ZONA PROSPEK HIDROKARBON BERDASARKAN INTEGRASI DATA SEISMIK DAN PETROFISIK DI LAPANGAN AULIA CEKUNGAN SUMATERA SELATAN - , Dian Novita Sari; , Prof. Dr. Sismanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A seismic data processing for mapping prospective hydrocarbon zone in Aulia field at South Sumatra Basin has been done by using seismic atribute such as root means square atribute and petrophysics. This study uses seismic attribute analysis and information of petrophyics water saturation and porosity, which aims to identify high amplitude anomaly zone, high porosity and low water saturation. By using that data, the presence of hydrocarbon zone can be shown. The analysis has been done by using the software PETREL 2008. The result from seismic attribute analysis using RMS amplitude is shown on the map of reservoir zone at Aulia 1 layer, with amplitude 50-80, which associated with 5-18 % porosity and water saturation of 30-60%. For Aulia 3 layer, the amplitude is 40-85, which associated with 3-29% porosity and saturation of 30-80%